Debugging the Link between Social Theory and Social Insects - Rodgers, Diane M., 1959- (Book collections on Project MUSE., 2008)
During the nineteenth and early twentieth centuries, natural and social scientists began comparing certain insects to human social organization. Entomologists theorized that social insects--such as ants, bees, wasps, and termites--organize themselves into highly specialized, hierarchical divisions of labor. Using a distinctly human vocabulary that reflected the dominant social structure of the time, they described insects as queens, workers, and soldiers and categorized their behaviors with words like marriage, slavery, farming, and factories. At the same time, sociologists working to develop a.